2016
DOI: 10.1021/acs.langmuir.6b02222
|View full text |Cite
|
Sign up to set email alerts
|

“Janus” Calixarenes: Double-Sided Molecular Linkers for Facile, Multianchor Point, Multifunctional, Surface Modification

Abstract: We herein report the synthesis of novel “Janus” calix[4]arenes bearing four “molecular tethering” functional groups on either the upper or lower rims of the calixarene. These enable facile multipoint covalent attachment to electrode surfaces with monolayer coverage. The other rim of the calixarenes bear either four azide or four ethynyl functional groups, which are easily modified by the copper(I)-catalyzed azide–alkyne cycloaddition reaction (CuAAC), either pre- or postsurface modification, enabling these con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 52 publications
0
26
0
Order By: Relevance
“…37,38 However, this can be prevented by using calix [4]arene-tetra-diazonium compounds whose structure and geometry do not allow any additional grafting. 39,40 These cone-shaped macrocycles can be grafted via multiple C-Au bonds, leading to a remarkably robust ligand shell on surfaces and on AuNPs. 39,41 Furthermore, because the grafting of these calix [4]arenes via C-Au bonds is irreversible, homogeneous mixtures of calixarenes can be grafted.…”
Section: Introductionmentioning
confidence: 99%
“…37,38 However, this can be prevented by using calix [4]arene-tetra-diazonium compounds whose structure and geometry do not allow any additional grafting. 39,40 These cone-shaped macrocycles can be grafted via multiple C-Au bonds, leading to a remarkably robust ligand shell on surfaces and on AuNPs. 39,41 Furthermore, because the grafting of these calix [4]arenes via C-Au bonds is irreversible, homogeneous mixtures of calixarenes can be grafted.…”
Section: Introductionmentioning
confidence: 99%
“…1). 4,[40][41][42][43][44][45][46][47] Calix [4]arenes are macrocycles composed of four phenolic units that are parasubstituted and linked in the ortho position through methylene bridges. These methylene bridges prevent polymerization of the diazonium derivatives, and hence lead solely to formation of monolayers.…”
Section: Introductionmentioning
confidence: 99%
“…Recently it has been shown that radical‐based electrografting processes are effective in preparing chemically modified electrodes to which molecules are covalently attached through an ethynyl group . We have previously described an assortment of methods whereby metallocenes derivatized at a cyclopentadienyl ring with a terminal ethynyl group can be covalently attached to carbon surfaces .…”
Section: Introductionmentioning
confidence: 99%
“…New directions and applications of anodic ethynyl deposition methods have already begun to appear. These include the depositions of a nickel cyclam complex that is an effective catalyst for CO 2 reduction, using the direct oxidation method, and several calixarenes anchored through multiple ethynyl groups, using the lithio activation method . Both Sheridan et al .…”
Section: Introductionmentioning
confidence: 99%